Constraining R-axion models through dijet searches at the LHC - Arganda Carreras, Ernesto (2019)
The search at hadron colliders for new massive resonances of a few 100 GeVs that couple effectively to colored states is an extremely challenging issue, due principally to the presence of large QCD multijet backgrounds at this energy, rendering the searches at the LHC particularly difficult. Recently, it was realized that these large backgrounds could be overcome by demanding one high-pT jet from initial-state radiation (ISR) and by means of novel jet-reconstruction techniques through which the resulting hadronized products of the massive resonances are reconstructed as a fat-jet, a unique large-radius jet. The ATLAS and CMS Collaborations have recently reported searches for the experimental signature of a single fat-jet in association with an ISR jet. Models of dynamical supersymmetry breaking with an spontaneously broken R-symmetry give rise to the appearance of a pseudo-Nambu?Goldstone boson called the R-axion, which naturally tends to be light. In the parameter space regions where the anomalous R-axion coupling to gluons is boosted, these models can be tested against these new LHC dijet searches. Taking into account the CMS search, we apply the qμ statistical method to the signal events against the background-only expectation and obtain the 95% C.L. exclusion limits on the most relevant model parameters for a particular messenger sector, namely, the R-axion mass ma, the decay constant fa, and the number of color messengers N, being these limits suitable to be applied to more general models with axion-like particles.